2019
DOI: 10.1002/jcla.23167
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum homocysteine level and unexplained infertility in in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI): A retrospective, hospital‐based, case‐control study

Abstract: Background: Lower serum homocysteine (Hcy) levels are found to correlate with a better chance of clinical pregnancy and better embryo grades in assisted reproductive technology (ART). However, there is little knowledge on the association between Hcy level and unexplained infertility until now. Methods:A total of 388 infertile women undergoing IVF/ICSI treatments were recruited, including 129 women with unexplained causes (case group) and 259 women with known causes (control group), and the case group was furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…This observation was in accordance with previous ndings that the pre-eclampsia women population has a higher level of TC than that in the normotensive group [14]. Serum homocysteine (HCY) has been reported to be a predict marker of pre-eclampsia and associated with IVF outcome [22,23]. In this research, although we observed an elevation of HCY level in the PE with IVF group in comparison to the PE group (P = 0.04), HCY levels in our 2 groups were both in the normal range.…”
Section: Glucose and Lipid Metabolism Were Not Signi Cantly Different...supporting
confidence: 93%
“…This observation was in accordance with previous ndings that the pre-eclampsia women population has a higher level of TC than that in the normotensive group [14]. Serum homocysteine (HCY) has been reported to be a predict marker of pre-eclampsia and associated with IVF outcome [22,23]. In this research, although we observed an elevation of HCY level in the PE with IVF group in comparison to the PE group (P = 0.04), HCY levels in our 2 groups were both in the normal range.…”
Section: Glucose and Lipid Metabolism Were Not Signi Cantly Different...supporting
confidence: 93%
“…Hcy, a sulfur-containing non-essential amino acid generated from the metabolism of the methionine and cysteine, plays a vital role in remethylation and trans-sulphuration. Previous studies have shown that a high serum Hcy level might lead to a reduction in the number of oocytes, suppress oocyte maturity, and reduce embryo quality (30)(31)(32). In order to reveal the correlation between AMH, PRL, Hcy, and embryo quality, a logistic regression analysis model was built for the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Hcy is an independent risk factor for atherogenic and thrombotic components in various systems [32,33]. In recent years, it is reported that Hcy is closely related to reproduction, such as PCOS [34-36], spontaneous abortion [37,38], IVF/ICSI results [39,40], unexplained infertility [41] and male sperm concentration [42].…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Liu found that although the serum Hcy level was signi cantly different between infertile patients and the normal group, it was not associated with the pregnancy outcome of IVF/ICSI. Thus, further research is needed [41]. Until up to now, there are still few studies on embryo quality and Hcy in elderly patients with DOR.…”
Section: Discussionmentioning
confidence: 99%